Integrating Social Accountability Approaches into Extractive Industries Projects : A Guidance Note - Heller, Katherine; van Wicklin III, Warren; Kumagai, Saki (World Bank, Washington, DC, 2016)
This note provides guidance on how to use social accountability (SA) approaches in oil, gas, and mining projects, with particular emphasis on World Bank projects in the extractive industry (EI) sectors. It highlights some consequences of poor transparency and accountability in EI sectors and identifies opportunities for addressing these issues. It demonstrates how the use of SA approaches and tools can improve the implementation and outcomes of EI projects. Although the note is written primarily for a World Bank/International Finance Corporation (IFC) audience and project cycle, it is hoped that it will be a resource for government, industry, and civil society partners as well.